2004
DOI: 10.1177/1038411104045362
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Citizenship and Human Resource Management: A New Tool or a Missed Opportunity?

Abstract: This paper examines the relationship between the social dimension of corporate citizenship (corporate community involvement) and human resource management. It begins by briefly reviewing the positive effects that corporate community involvement can have on human resource management outcomes such as employee motivation, morale, commitment, recruitment, retention, development and teamwork. It presents findings that the human resource management function is not playing a significant role with respect to decisionm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 14 publications
2
40
0
2
Order By: Relevance
“…Many scholars point out the strong influence of CSR and business' ethical environment on employees' job attitudes. These include employees' motivation and morale (Basil and Weber, 2006;Branco and Rodrigues, 2006;Zappala, 2004), job satisfaction, organizational commitment, and loyalty to the firm (Branco and Rodrigues, 2006;Collier and Esteban, 2007;Tsai and Huang, 2008). Through CSR, employers can provide employees with opportunities to thoughtfully participate in the management of company affairs and to contemplate the ultimate meaning of things; for example, the good life and virtue beyond pursuit of wealth (Bragues, 2006), and contribute to the formation of a morally driven community.…”
Section: Stakeholders and The Socially Responsible Organizationmentioning
confidence: 98%
“…Many scholars point out the strong influence of CSR and business' ethical environment on employees' job attitudes. These include employees' motivation and morale (Basil and Weber, 2006;Branco and Rodrigues, 2006;Zappala, 2004), job satisfaction, organizational commitment, and loyalty to the firm (Branco and Rodrigues, 2006;Collier and Esteban, 2007;Tsai and Huang, 2008). Through CSR, employers can provide employees with opportunities to thoughtfully participate in the management of company affairs and to contemplate the ultimate meaning of things; for example, the good life and virtue beyond pursuit of wealth (Bragues, 2006), and contribute to the formation of a morally driven community.…”
Section: Stakeholders and The Socially Responsible Organizationmentioning
confidence: 98%
“…However, employee and corporate benefits from participation in volunteering have also been established (see for example, Tuffrey, 1997;Zappala, 2004). In addition to providing an opportunity to gain professional and interpersonal skills, CV programs also have positive effects on attitudes and behaviours towards employers, including enhanced motivation, commitment and job satisfaction (Gilder et al, 2005).…”
Section: Corporate Volunteeringmentioning
confidence: 99%
“…Crucially, over the course of time, research has indicated that if managed effectively, community initiatives could assist companies in retaining and even increasing their customers (Levy, 2005;Simmons and Becker-Olsen, 2006), fostering a sense of commitment from employees (De Gilder et al, 2005;Grayson, 1993;Zappala, 2004) and strengthening their corporate reputation as a 'caring business' (Arendt and Brettel, 2010;Brammer and Millington, 2005;Brammer and Pavelin, 2005;Hillenbrand and Money, 2007). As a result, community initiatives have come to be perceived more as strategic activities rather than voluntary or discretionary (Saiia et al, 2003): that is to say, not legally mandated but strategically essential.…”
Section: Corporate Social Responsibility: Discretionary Strategic Ormentioning
confidence: 99%